2022
DOI: 10.1002/fes3.389
|View full text |Cite
|
Sign up to set email alerts
|

Short planks in the crop nutrient barrel theory of China are changing: Evidence from 15 crops in 13 provinces

Abstract: Large quantities of fertilizers, mainly nitrogen (N), phosphorus (P), and potassium (K), are used in China's crop production; however, whether N, P, and K still limit yield under the current high input remains unknown. In addition, it is not clear whether magnesium (Mg) potentially limits crop production. To address these issues, a national survey of the soil nutrient status and farmers' fertilization practices was conducted in China to determine the soil N, P, K, and Mg status and current fertilization practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 154 publications
0
8
0
Order By: Relevance
“…Magnesium (Mg) deficiency is increasingly observed in intensive crop production systems and becomes an important limiting factor to plant growth after nitrogen, phosphorus, and potassium, especially in soils with low pH, high leaching potential or intensively fertilized with potassium (Cakmak & Yazi̇ci̇, 2010; Chen et al., 2022; Gransee & Führs, 2013; Wang et al., 2020). Leaf interveinal chlorosis, as one of the typical symptoms of plants affected by Mg deficiency stress, is highly dependent on light intensity (Cakmak & Marschner, 1992; Cakmak & Yazi̇ci̇, 2010; Hermans & Verbruggen, 2005; Peng et al., 2019; Tränkner et al., 2018; Verbruggen & Hermans, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium (Mg) deficiency is increasingly observed in intensive crop production systems and becomes an important limiting factor to plant growth after nitrogen, phosphorus, and potassium, especially in soils with low pH, high leaching potential or intensively fertilized with potassium (Cakmak & Yazi̇ci̇, 2010; Chen et al., 2022; Gransee & Führs, 2013; Wang et al., 2020). Leaf interveinal chlorosis, as one of the typical symptoms of plants affected by Mg deficiency stress, is highly dependent on light intensity (Cakmak & Marschner, 1992; Cakmak & Yazi̇ci̇, 2010; Hermans & Verbruggen, 2005; Peng et al., 2019; Tränkner et al., 2018; Verbruggen & Hermans, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium (Mg) is ‘the forgotten element’ in crop production (Cakmak & Yazici, 2010) and has become a nutritional obstacle in crop yield and quality (Chen et al, 2022; Wang et al, 2019). In China, a national soil and plant nutrition survey showed that the limiting factor on crop yields and quality has shifted from NPK to Mg (Chen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium (Mg) is ‘the forgotten element’ in crop production (Cakmak & Yazici, 2010) and has become a nutritional obstacle in crop yield and quality (Chen et al, 2022; Wang et al, 2019). In China, a national soil and plant nutrition survey showed that the limiting factor on crop yields and quality has shifted from NPK to Mg (Chen et al, 2022). A decrease in plant dry matter (DM) because of Mg deficiency has been observed in various plants, including tomato (Li et al, 2018), citrus (Wang et al, 2022), rice (Tanoi et al, 2014) and Arabidopsis (Mao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations